Left Ventricular Remodeling and Myocardial Work: Results From the Population-Based STAAB Cohort Study - Sahiti, Floran; Morbach, Caroline; Cejka, Vladimir; Albert, Judith; Eichner, Felizitas A.; Gelbrich, Götz; Heuschmann, Peter U.; Störk, Stefan (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Left ventricular (LV) dilatation and LV hypertrophy are acknowledged precursors of myocardial dysfunction and ultimately of heart failure, but the implications of abnormal LV geometry on myocardial function are not well-understood. Non-invasive LV myocardial work (MyW) assessment based on echocardiography-derived pressure-strain loops offers the opportunity to study detailed myocardial function in larger cohorts. We aimed to assess the relationship of LV geometry with MyW indices in general population free from heart failure. Methods and Results: We report cross-sectional baseline data from the Characteristics and Course of Heart Failure Stages A-B and Determinants of Progression (STAAB) cohort study investigating a representative sample of the general population of Würzburg, Germany, aged 30–79 years. MyW analysis was performed in 1,926 individuals who were in sinus rhythm and free from valvular disease (49.3% female, 54 ± 12 years). In multivariable regression, higher LV volume was associated with higher global wasted work (GWW) (+0.5 mmHg% per mL/m2, p < 0.001) and lower global work efficiency (GWE) (−0.02% per mL/m2, p < 0.01), while higher LV mass was associated with higher GWW (+0.45 mmHg% per g/m2, p < 0.001) and global constructive work (GCW) (+2.05 mmHg% per g/m2, p < 0.01) and lower GWE (−0.015% per g/m2, p < 0.001). This was dominated by the blood pressure level and also observed in participants with normal LV geometry and concomitant hypertension. Conclusion: Abnormal LV geometric profiles were associated with a higher amount of wasted work, which translated into reduced work efficiency. The pattern of a disproportionate increase in GWW with higher LV mass might be an early sign of hypertensive heart disease.